(untitled) (Architecture Image Studies, 2025)
Architecture is the embodiment of an ongoing discourse among socio-cultural, techno-legal commentaries, radical discovery, technological innovations, political processes, and artistic expressions; per say. It addresses the problems of enclosure, connectivity, permanence, usage, organization, aesthetics, and structure. Further, digital technologies, emergence of regulatory authorities, response to climate change and its effects, growing energy and water needs cannot be ignored. Dwindling economy, dropping pay packages, loss of jobs etc are the concerns that shape the future of investments in architecture. In the light of such crucial conditions, architects need to be accountable; not only to clients, but to the society and governments at large. Performing Aesthetics thus emerge as the only panacea for this scenario that is not bright, but gloomy. While mass consumerism, standardization, and mass production were the buzzwords of the second industrial revolution, where performance and efficiency are crucial, the first industrial age focused on the need for machinery and mechanization in both production and construction. Furthermore, post-modernism emerged as a result of mass production monotony. Architecture is preparing for mass consumption in the future, with 3-D printing allowing for mass customization and online building transfers in the form of electronic data. However, there are very few academic conversations that incorporate explanatory theory and aesthetic education. The development of performing aesthetics that stresses the improved "worth and value" for money—the primary focus of the current situation worldwide—requires the identification of a suitable definition as well as the contributing elements and characteristics. The goal of this study is to identify a novel strategy for creating "Architecture 2.0 which generates aesthetically enriched productions" for the future of technology and building design.